2012
DOI: 10.1111/j.1551-2916.2011.05046.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Mono‐Vacancy and Oxygen Permeability in Y2SiO5 Orthosilicate Studied by First‐Principles Calculations

Abstract: Understanding the mechanisms of native point defects and oxygen‐vacancy diffusion in Y2SiO5 is important to evaluate its performance as environmental and thermal barrier coating (ETBC). In the present first‐principles calculations, we show that oxygen vacancy is the predominant vacancy species and prefers to form on the oxygen lattice sites inside SiO4 tetrahedra instead of on the interstitial non‐silicon‐bonded oxygen site. The calculated defect formation energy and concentration of mono‐vacancies in Y2SiO5 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 56 publications
1
50
1
Order By: Relevance
“…predicted that Y 2 Si 2 O 7 is a damage tolerant silicate and proved it by experimental study of mechanical properties . Very recently, the present authors showed the mechanisms of monovacancy and extremely low oxygen permeability in Y 2 SiO 5 by first‐principles calculation . In this article, we focus on all possible native point defects and mechanisms of nonstoichiometry of Y 2 SiO 5 and Y 2 Si 2 O 7 .…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…predicted that Y 2 Si 2 O 7 is a damage tolerant silicate and proved it by experimental study of mechanical properties . Very recently, the present authors showed the mechanisms of monovacancy and extremely low oxygen permeability in Y 2 SiO 5 by first‐principles calculation . In this article, we focus on all possible native point defects and mechanisms of nonstoichiometry of Y 2 SiO 5 and Y 2 Si 2 O 7 .…”
Section: Introductionmentioning
confidence: 71%
“…To pace the first step to study the mechanism of defects, one need to determine the preferred position of an isolated native point defect for the later case. In our previous work about the monovacancy in Y 2 SiO 5 , the most stable vacancy sites of oxygen and yttrium are reported at the O 1 and Y 1 sites, respectively . To determine the possible interstitial site, we follow the calculation strategy used in Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous first‐principles investigation of point defects in YAG used the same primitive cell and obtained reasonable results . Furthermore, this distance is supposed to be large enough to exclude self‐interaction of many point defects in the first‐principles calculations …”
Section: Calculation Methodsmentioning
confidence: 92%
“…15) Li et al reported the synthesis of bulk Al 3 BC 3 by reactive hot pressing and proposed the synthesis mechanism as solid-solid reactions. 14) Metal carbides have been prepared by the carbo-thermal reduction of metal oxides, direct reaction between metal elements and carbon, and the gas phase reaction of metal-containing gases and appropriate hydrocarbons. 17) Among the processes, carbo-thermal reduction of metal oxides is the most commonly used route for industrial production due to inexpensive raw materials and simple process.…”
Section: )4)mentioning
confidence: 99%